Organic fertilizers and bauxite residue on nutrient availability and nutrition of sugar cane irrigated with potable water and wastewater - de Nobile, Fabio Olivieri; Galbiatti, João Antonio; Muraishi, Reginaldo Itiro (Comunicata Scientiae, 2012)
The objective of this study was to evaluate the effect of organic fertilizers (urban solid waste and swine manure) as a source of nutrients and residue from bauxite processing as a corrective of soil acidity, in area cultivated with sugar cane irrigated with potable water and served in the availability of phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S) levels in the soil and plants. For this experiment was carried out in pots, using a Alfisol, assessing the availability of the elements in the 0-20 cm layer and the concentration of these nutrients in the leaves of sugarcane. The data showed that the residues increased the concentrations of Ca and Mg in soil, as the concentration of K was not changed and S was not detected, due to the low concentration in the soil. In the leave +1 of sugarcane the residue of bauxite increased levels of N, P, K, Ca and Mg (15.68, 1.73, 10.43, 3.50 and 1.08 g kg-1, respectively). The application of urban solid waste and swine manure also increased the levels of N, K and Ca (11.56, 9.18 and 2.81 g kg-1, respectively). The quality of irrigation water did not alter the availability of P, K, Ca, Mg and S in the soil as well as the levels of these macronutrients in the plant.